2016
DOI: 10.7150/jca.13422
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nuclear PIM1 Expression with Lymph Node Metastasis and Poor Prognosis in Patients with Lung Adenocarcinoma and Squamous Cell Carcinoma

Abstract: Increasing evidence indicates that aberrant expression of PIM1, p-STAT3 and c-MYC is involved in the pathogenesis of various solid tumors, but its prognostic value is still unclear in non-small cell lung cancer (NSCLC). Here, we sought to evaluate the expression and prognostic role of these markers in patients with lung adenocarcinoma (AD) and squamous cell carcinoma (SCC). Real time RT-PCR and Western blotting was used to analyze the mRNA and protein expression of PIM1 in NSCLC cell lines, respectively. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Moreover, expression of CAIX, a hypoxia-inducible gene, significantly increased following treatment, indicating that anti-VEGF agents increase hypoxia in these tumors (Fig S1). Consistent with previous reports, PIM1 protein exhibited a nuclear staining pattern with variable cytoplasmic staining (37, 38). Treatment with B20 or sunitinib significantly increased PIM1 levels compared to vehicle treatment, reaching over 60% positive staining following B20 treatment (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, expression of CAIX, a hypoxia-inducible gene, significantly increased following treatment, indicating that anti-VEGF agents increase hypoxia in these tumors (Fig S1). Consistent with previous reports, PIM1 protein exhibited a nuclear staining pattern with variable cytoplasmic staining (37, 38). Treatment with B20 or sunitinib significantly increased PIM1 levels compared to vehicle treatment, reaching over 60% positive staining following B20 treatment (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Finally, a total of 13 eligible studies were included in this meta-analysis (flowchart in Fig 1 , Fig 1 in the S1 File ). Eight of these studies were analyzed to determine the correlation of p-STAT3 overexpression with the overall survival of lung cancer patients [ 15 , 22 , 24 , 26 30 ]. And ten studies were subjected to the meta-analysis of clinicopathological characteristics [ 31 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that p-STAT3 overexpression is associated with poorer prognosis in patients with gastric cancer [ 18 ], colorectal carcinoma [ 19 ], pancreatic cancer [ 20 ], and lung cancer [ 21 ]. However, no association between p-STAT3 overexpression and lung cancer development has been found in some recent studies [ 22 24 ]. Therefore, we conducted this updated meta-analysis to explore the correlation between p-STAT3 overexpression and the overall survival of lung cancer patients, as well as other clinicopathological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…14 It is overexpressed in many types of cancer cells, including hepatocellular cancer, prostate cancer, glioblastoma, lung cancer, breast cancer and CRC, and its overexpression is associated with tumor development and progression. 13,[15][16][17][18][19] In colon cancer, Pim1 repression leads to major changes in oncogenic signal transduction with regard to p21 Cip1/WAF1 , STAT3, JNK, c-Myc, and survivin and in the levels of apoptosis-related proteins Puma, Bax, and Bcl-xL. 19 However, the underlying mechanism of Pim1 in CRC remains unclear.…”
Section: Introductionmentioning
confidence: 99%